PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN MUTU LAYANAN TERHADAP KEPUASAN NASABAH DI BANK MEGA TANGERANG - Dudung Hadiwijaya; Hendi Eka Sumarga (Universitas Muhammadiyah Tangerang, 2019)
The purpose of the research is to examine the influence of the human resource competensy and service quality to the customer satisfaction of the Bank Mega Tangerang. The result of the research indicate that the human resources competency and service quality are together have significant effect toward the customer satisfaction. The result also indicates that the human resources competency have more dominant and significant effect than service quality towards the customer satisfaction of Bank Mega Tangerang.Keywords: human resources competency, service quality, customer satisfaction